The Benefits of Halal Labels to Encourage Purchasing Desire in The Culinary Business - Nadaraniya; Heri Prasetyo (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2026)
This study aims to find out how influential the Halal Label is on Sadasa Catering's customers' purchase decisions. This study uses a survey method with a sample of 85 regular customers of Sadasa Catering, the data is analyzed using the Statistical Package for the Social Sciences (SPSS) version 26 with a simple linear regression analysis technique. The results of the study showed a significant value of 0.000 which is smaller than 0.05 which means that the Halal Label has an effect on the purchase decision. This shows that the availability of halal labels plays a significant role in influencing Sadasa Catering's customers' purchasing decisions. Although the impact is negative, it shows that in addition to the halal label factor, customers also consider other factors that are not included in this study. In addition, companies must consider other elements that influence customer choice. This research can be used as a reference by companies to increase product sales.